Heightened cocaine-seeking in male rats associates with a distinct transcriptomic profile in the medial prefrontal cortex - Merritt, Christina R.; Smith, Ashley E.; Khanipov, Kamil; Golovko, George; Dineley, Kelly T.; Anastasio, Noelle C.; Cunningham, Kathryn A. (Frontiers in Pharmacology, 2022)
Drug overdose deaths involving cocaine have skyrocketed, an outcome attributable in part to the lack of FDA-approved medications for the treatment of cocaine use disorder (CUD), highlighting the need to identify new pharmacotherapeutic targets. Vulnerability to cocaine-associated environmental contexts and stimuli serves as a risk factor for relapse in CUD recovery, with individual differences evident in the motivational aspects of these cues. The medial prefrontal cortex (mPFC) provides top-down control of striatal circuitry to regulate the incentive-motivational properties of cocaine-associated stimuli. Clinical and preclinical studies have identified genetic variations that impact the degree of executive restraint over drug-motivated behaviors, and we designed the present study to employ next-generation sequencing to identify specific genes associated with heightened cue-evoked cocaine-seeking in the mPFC of male, outbred rats. Rats were trained to stably self-administer cocaine, and baseline cue-reinforced cocaine-seeking was established. Rats were phenotyped as either high cue (HC) or low cue (LC) responders based upon lever pressing for previously associated cocaine cues and allowed 10 days of abstinence in their home cages prior to mPFC collection for RNA-sequencing. The expression of 309 genes in the mPFC was significantly different in HC vs. LC rats. Functional gene enrichment analyses identified ten biological processes that were overrepresented in the mPFC of HC vs. LC rats. The present study identifies distinctions in mPFC mRNA transcripts that characterizes individual differences in relapse-like behavior and provides prioritized candidates for future pharmacotherapeutics aimed to help maintain abstinence in CUD. In particular the Htr2c gene, which encodes the serotonin 5-HT2C receptor (5-HT2CR), is expressed to a lower extent in HC rats, relative to LC rats. These findings build on a plethora of previous studies that also point to the 5-HT2CR as an attractive target for the treatment of CUD.